Isotopic and geochemical constraints on lead and fluid sources of the PbZnAg mineralization in the polymetallic Tighza-Jbel Aouam district (central Morocco), and relationships with the geodynamic context. (March 2017) - Rossi, Magali; Gasquet, Dominique; Cheilletz, Alain; Tarrieu, Leïla; Bounajma, Hassan; Mantoy, Tristan; Reisberg, Laurie; Deloule, Etienne; Boulvais, Philippe; Burnard, Pete
Abstract: The WAu, PbZnAg, and SbBa mineralizations of the polymetallic Tighza-Jbel Aouam district (central Meseta, Morocco), are hosted in Paleozoic rocks surrounding late-Carboniferous granitic stocks. The PbZnAg Tighza deposit formed at 254 ± 16 Ma, and is clearly disconnected from the late-Variscan WAu deposit (295-280 Ma). The PbZnAg mineralization precipitated from a complex hydrothermal fluid. It displays air-normalized 3 He/ 4 He ratio (0.018–0.103) typical of the upper crust. This crustal component is confirmed by the oxygen and carbon isotope compositions (δ 18 O = +19 to +25‰; δ 13 C = −3.6 to −11.2‰) and the ɛNd values (−4.84 to −9.01) of gangue carbonates, which show mixing of (i) fluids that have interacted with late-Carboniferous magmatic rocks, and (ii) fluids in equilibrium with the Paleozoic metasediments. In addition, the PbZnAg mineralization has 40 Ar/ 36 Ar values in the range 284–315 typical of a meteoric fluid. The radiogenic Pb isotopic compositions ( 207 Pb/ 204 Pb = 15.70–15.80 and 206 Pb/ 204 Pb = 18.30–18.50) suggest leaching of Pb from the surrounding Paleozoic metasediments and late-Variscan granites, whereas the low radiogenic signatures ( 207 Pb/ 204 Pb = 15.40 and 206 Pb/ 204 Pb = 18.05) provide evidence of a deeper source attributed to the lower crust. Crustal thinning related to extensional tectonics in late-Permian and Early-Triassic lead to high-K calc-alkaline to alkaline magmatic activity, which is evidenced by a dense SW-NE-trending dike network that pre-dated the Atlantic Ocean opening (early Liassic times). This magmatic event induced a regional heat flux increase that triggered the circulation of a complex hydrothermal fluid, which has a strong crustal component, but also a meteoric and a lower crustal components. The polymetallic district of Tighza-Jbel Aouam thus results from superposition of an intrusion related porphyry-gold mineralization (WAu, 286 Ma) followed by a PbZnAg epithermal mineralization (254 Ma), during two distinct magmatic-hydrothermal events. The proposed metallogenic model for the PbZnAg Tighza-Jbel Aouam deposit provides new constraints for the PbZnAg exploration in the Moroccan Meseta. Exploration targets must take into account the following geological features: (i) Permo-triassic high-K calk-alkaline to alkaline dikes, (ii) extensional tectonics and reactivation of ancient crust-scale faults and shear zones, and (iii) Paleozoic series containing organic matter (e.g., black shales) subjected to low grade metamorphism (e.g., greenschist facies). Highlights: PbZnAg vein-type mineralization disconnected from adjacent late-Variscan granites. Epithermal PbZnAg veins related to Permo-Triassic extension and magmatic activity. Complex hydrothermal system resulting from mixing various crustal fluids. A new metallogenic model for PbZnAg veins and new exploration guides.